2014
DOI: 10.4238/2014.may.23.13
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the drought-resistance OsRCI2-5 gene in rice (Oryza sativa L.)

Abstract: ABSTRACT. The genomic expression profile of the super-hybrid rice Liangyoupeijiu female parent Pei'ai 64S in different tissues at different developmental stages under low temperature, drought, and high temperature stresses were detected using an Affymetrix GeneChip Rice Genome Array to screen upregulated and downregulated genes. In this study, we screened the drought-resistant gene OsRCI2-5, after which a constitutive OsRCI2-5 construct was created and transferred into Nipponbare. After polyethylene glycol-600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In this study, we identified MePMP3-2 by searching sequences with similarity to the rice gene OsRCI2-5. OsRCI2-5 is a stress-responsive gene of rice and, when over-expressed, greatly enhances drought tolerance of transgenic rice (Li et al, 2014). The results of our studies show that MePMP3-2 is induced by salt and drought stresses.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…In this study, we identified MePMP3-2 by searching sequences with similarity to the rice gene OsRCI2-5. OsRCI2-5 is a stress-responsive gene of rice and, when over-expressed, greatly enhances drought tolerance of transgenic rice (Li et al, 2014). The results of our studies show that MePMP3-2 is induced by salt and drought stresses.…”
Section: Introductionmentioning
confidence: 57%
“…In this study, a gene homologous to the stress-inducible OsRCI2-5 (Li et al, 2014), MePMP3-2, was isolated for the first time from cassava and its expression was shown to increase in response to salt and drought stresses. Like OsRCI2-5, the predicted MePMP3-2 protein was found to belong to the PMP3 family of small membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations